Employing Technology in Digital Advertising Design and its Creative Representations in the Products of Art Education Students (The International Journal for Scientific Research, 2024)
The research dealt with the topic of (employing technology in the design of digital advertising and its creative representations in the products of art education students). The research contained four chapters. The first chapter dealt with: the methodological framework of the research, represented by the research problem that was revealed in the following question: How has technology contributed to employment in the design of digital advertising? They have no role in enriching the creative process and are represented in their artistic productions. The researcher determined the limits of the research, which were represented by the products of the students of the Department of Art Education - First Stage / College of Fine Arts/ University of Baghdad for the academic year (2020-2021), and then the researcher moved to the second semester, which included two sections. The title of the first section was employing technology artistically for advertising, and the section included the second is the creative process and aesthetic standards in the artistic achievement, and the researcher extracted a number of indicators that resulted from the theoretical framework:1.  The use of digital technical methods in employing shapes by following the technique of assembling and composing photographs, and generating a main rhythm between images and color values, served the functional aspect and the creative process of the advertising poster.2.  The computer showed a kind of diversity and excitement in the use of letters and their formal formulation in the design space. Among the most important conclusions is that the use of digital technology in the field of art education for practical academic subjects has given students the ability to diversify the styles of artistic production and facilitate the procedures used in producing these artistic works.
Keywords: Implement; Technology; Design; Digital Advertising; The Creative Process